The prospective association between total and type of fish intake and type 2 diabetes in 8 European countries: EPIC-InterAct Study. - Patel, P; Forouhi, N; Kuijsten, A; Schulze, M; van Woudenbergh, G; Ardanaz, E; Amiano, P; Arriola, L; Balkau, B; Barricarte, A; Beulens, J; Boeing, H; et al. (2012)
BACKGROUND: Epidemiologic evidence of an association between fish intake and type 2 diabetes (T2D) is inconsistent and unresolved. OBJECTIVE: The objective was to examine the association between total and type of fish intake and T2D in 8 European countries. DESIGN: This was a case-cohort study, nested within the European Prospective Investigation into Cancer and Nutrition (EPIC) study, with 3.99 million person-years of follow-up, 12,403 incident diabetes cases, and a random subcohort of 16,835 individuals from 8 European countries. Habitual fish intake (lean fish, fatty fish, total fish, shellfish, and combined fish and shellfish) was assessed by country-specific dietary questionnaires. HRs were estimated in each country by using Prentice-weighted Cox regression models and pooled by using a random-effects meta-analysis. RESULTS: No overall association was found between combined fish and shellfish intake and incident T2D per quartile (adjusted HR: 1.00; 95% CI: 0.94, 1.06; P-trend = 0.99). Total fish, lean fish, and shellfish intakes separately were also not associated with T2D, but fatty fish intake was weakly inversely associated with T2D: adjusted HR per quartile 0.97 (0.94, 1.00), with an HR of 0.84 (0.70, 1.01), 0.85 (0.76, 0.95), and 0.87 (0.78, 0.97) for a comparison of the second, third, and fourth quartiles with the lowest quartile of intake, respectively (P-trend = 0.06). CONCLUSIONS: These findings suggest that lean fish, total fish, and shellfish intakes are not associated with incident diabetes but that fatty fish intake may be weakly inversely associated. Replication of these findings in other populations and investigation of the mechanisms underlying these associations are warranted. Meanwhile, current public health recommendations on fish intake should remain unchanged.